IKTIOFAUNA PERAIRAN TAWAR DI KAWASAN TAMAN NASIONAL BOGANI NANI WARTABONE DAN SEKITARNYA, GORONTALO-SULAWESI UTARA - Rusdianto Rusdianto; Sopian Sauri (Research Center for Biology-Indonesian Institute of Sciences, 2021)
ABSTRACT TNBNW is included in the Wallacea Region which is a transitional zone between Oriental and Australian zoogeography which is estimated to have many unique and endemic flora and fauna species, including fish species that have not been fully disclosed. This study aims to inventory the diversity of ichthyofauna that live in the fresh waters of the TNBNW area and its surroundings. Sampling was carried out by making 11 research stations from the waters that flow from the Matabulawa peak to the Bone River. Samples were collected by electrofishing then identified and preserved using formalin solution. The species of fish obtained were analyzed on the index of diversity, evenness, and species richness. To complete the data, tabulation of data on fish species in the TNBNW area from previous studies as well as specimens that already have catalog numbers deposited in MZB was carried out. This study found 13 species of fish consisting of 6 families and 10 genera. The total ichthyofauna in the TNBNW area and its surroundings is 32 species consisting of 15 families. Stiphodon sp. is the species that has the highest relative abundance (48.80), followed by Poecilia reticulata (11.00). The species with the highest local distribution was Belobranchus belobranchs (90.91%). The rivers that have the highest index of species diversity, evenness, and species richness are Pilolode River, Pilohampaa River, and Loji River, respectively. Two species are classified as introduced fish, namely Poecilia reticulata and Oreochromis niloticus. Several species of fish have potential as ornamental fish as well as consumption fish. Key words: Species diversity, ichthyofauna, TNBNW ABSTRAKTNBNW termasuk ke dalam Kawasan Wallacea yang merupakan zona peralihan antara zoogeografi Oriental dan Australia yang diperkirakan memiliki banyak jenis flora dan fauna yang unik dan endemik, termasuk jenis-jenis ikan yang belum semua dapat diungkapkan. Penelitian ini bertujuan untuk menginventarisasi keragaman iktiofauna yang hidup di perairan tawar kawasan TNBNW dan sekitarnya. Sampling dilakukan dengan membuat 11 stasiun penelitian dari perairan yang mengalir dari puncak Matabulawa menuju Sungai Bone. Sampel dikoleksi dengan elektrofishing kemudian diidentifikasi dan dipreservasi menggunakan larutan formalin. Jenis ikan yang diperoleh dianalisis indeks keanekaragaman, kemerataan dan kekayaan jenisnya. Untuk melengkapi data, dilakukan tabulasi data jenis-jenis ikan di kawasan TNBNW dari penelitian-penelitian sebelumnya serta spesimen yang telah terkatalog yang terdeposit di MZB. Penelitian ini menemukan 13 jenis ikan yang terdiri dari 6 famili dan 10 genus. Total iktiofauna di kawasan TNBNW dan sekitarnya adalah 32 jenis, terdiri dari 15 famili. Stiphodon sp. merupakan jenis yang memiliki kelimpahan relatif tertinggi (48,80) diikuti Poecilia reticulata (11,00). Jenis yang memiliki distribusi lokal tertinggi adalah Belobranchus belobranchus (90,91%). Sungai yang memiliki indeks keanekaragaman jenis, kemerataan dan kekayaan jenis paling tinggi masing-masing adalah Sungai Pilolode, Sungai Pilohampaa dan Sungai Loji. Dua jenis ikan tergolong ikan introduksi yaitu Poecilia reticulata dan Oreochromis niloticus. Beberapa jenis ikan memiliki potensi sebagai ikan hias dan juga ikan konsumsi. Kata Kunci: Keragaman jenis, iktiofauna, TNBNW